Genome Editing in Mice Using CRISPR/Cas9 Technology. Issue 1 (4th September 2018) - Hall, Bradford; Cho, Andrew; Limaye, Advait; Cho, Kyoungin; Khillan, Jaspal; Kulkarni, Ashok B.
Abstract: CRISPR/Cas9 technology has revolutionized genome editing in mice, allowing for simple and rapid development of knockouts and knockins. CRISPR relies on small guide RNAs that direct the RNA‐guided nuclease Cas9 to a designated genomic site using ∼20 bp of corresponding sequence. Cas9 then creates a double‐strand break in the targeted loci that is either patched in an error‐prone fashion to produce a frame‐shift mutation, a knockout, or is repaired by recombination with donor DNA containing homology arms, a knockin. This protocol covers the techniques needed to rapidly generate knockout and knockin mice with CRISPR via microinjection of Cas9, the guide RNA, and possible donor DNA into the mouse zygote. © 2018 by John Wiley & Sons, Inc.